1975
DOI: 10.1152/jappl.1975.38.6.974
|View full text |Cite
|
Sign up to set email alerts
|

Changes in lung mechanics during asthma induced by exercise

Abstract: Pulmonary and airway mechanics were assessed in seven asthmatic patients in remission, when asthma was induced by exercise and again after spontaneous recovery or bronchodilator treatment. After exercise there was a sustained fall in forced expiratory volume in 1 s (FEV 1.0) in all patients, varying from 30 to 80 percent of the initial value. Total lung capacity (TLC) increased significantly in four of the seven patients. In one of the four patients the increase in TLC was associated with an increase in stati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
1

Year Published

1978
1978
2000
2000

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 69 publications
(34 citation statements)
references
References 0 publications
1
32
0
1
Order By: Relevance
“…In a group of children Benatar & Konig (6) found that EIA caused similar and significant changes in both crude and sensitive tests of lung function, but of particular interest was an increase in residual volume, fall in flow rates in the terminal part of the flow-volume curve and a decrease in the slope of the curve, which they felt indicated closure of some lung units. Similar conclusions were reached by Freedman et al (20) in a study of adults with EIA, but they also noted a substandal increase in total lung capacity in some subjects with a parallel shift of the pressure-volume curve to the left suggesting decreased elasdc recoil, closure of lung units and widespread airway narrowing.…”
Section: The Site Of Constriction In Eiasupporting
confidence: 83%
See 1 more Smart Citation
“…In a group of children Benatar & Konig (6) found that EIA caused similar and significant changes in both crude and sensitive tests of lung function, but of particular interest was an increase in residual volume, fall in flow rates in the terminal part of the flow-volume curve and a decrease in the slope of the curve, which they felt indicated closure of some lung units. Similar conclusions were reached by Freedman et al (20) in a study of adults with EIA, but they also noted a substandal increase in total lung capacity in some subjects with a parallel shift of the pressure-volume curve to the left suggesting decreased elasdc recoil, closure of lung units and widespread airway narrowing.…”
Section: The Site Of Constriction In Eiasupporting
confidence: 83%
“…The changes in crude tests of lung function such as the PEFR and FEV, implicate gross changes in larger airnays, but changes in lung recoil pressure or closure of lung units could also be involved (20). In a group of children Benatar & Konig (6) found that EIA caused similar and significant changes in both crude and sensitive tests of lung function, but of particular interest was an increase in residual volume, fall in flow rates in the terminal part of the flow-volume curve and a decrease in the slope of the curve, which they felt indicated closure of some lung units.…”
Section: The Site Of Constriction In Eiamentioning
confidence: 99%
“…In a subsequent study [28] based on plethysmographic measurements, the falls in FRC during recovery and the proportion of patients showing a reduction in TLC were even greater. Other studies suggested acute increases in TLC (measured plethysmographically) following exercise challenge [29,30] and inhalation of histamine [31]. WOOLCOCK and co-workers [28] had originally acknowledged the possibility that plethysmographic volume measurement might be an overestimate if changes in mouth pressure did not correspond to changes in alveolar pressure.…”
Section: Lung Volumesmentioning
confidence: 99%
“…Based on the inflammatory theory of asthma, it was hypothesised that this was due, not only to an increase in airway calibre [23][24][25], but also to a reduction in peribronchial and alveolar inflammation [26] which, when present, causes a temporary loss of the relationship between small bronchi and parenchyma, thus reducing elastic recoil [27,28]. This is suggested in this study by the fact that a small improvement in airway calibre after budesonide, demonstrated by the increase in sG aw , was not accompanied by a change in RV, which remained higher and not different from placebo.…”
Section: Discussionmentioning
confidence: 99%